2022
DOI: 10.1186/s40643-021-00490-3
|View full text |Cite
|
Sign up to set email alerts
|

Paper mulberry fruit juice: a novel biomass resource for bioethanol production

Abstract: By way of broadening the use of diverse sustainable bioethanol feedstocks, the potentials of Paper mulberry fruit juice (PMFJ), as a non-food, sugar-based substrate, were evaluated for fuel ethanol production. The suitability of PMFJ was proven, as maximum ethanol concentration (56.4 g/L) and yield (0.39 g/g) were achieved within half a day of the start of fermentation, corresponding to very high ethanol productivity of 4.7 g/L/hr. The established potentials were further optimally maximized through the respons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Woody plants have multiple uses (Figure 2), mainly as edible and medicinal products, but also as feed, compost, bioenergy and fiber products (Jitjaicham and Kusuktham, 2016;Wen et al, 2018;Hao et al, 2020;Ajayo et al, 2022). Because the fresh branches and leaves of woody plants are rich in nutrients and functional components, they can be used as a potential feed resource with additional value (Du et al, 2021b).…”
Section: Distribution and Multifunctional Utilization Of Woody Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…Woody plants have multiple uses (Figure 2), mainly as edible and medicinal products, but also as feed, compost, bioenergy and fiber products (Jitjaicham and Kusuktham, 2016;Wen et al, 2018;Hao et al, 2020;Ajayo et al, 2022). Because the fresh branches and leaves of woody plants are rich in nutrients and functional components, they can be used as a potential feed resource with additional value (Du et al, 2021b).…”
Section: Distribution and Multifunctional Utilization Of Woody Plantmentioning
confidence: 99%
“…of soluble sugars (Han et al, 2016), which are usually shed at maturity and decay on the ground, resulting in the loss of these resources. Using the fruits of these woody plants as a feedstock, biotechnology has been successfully developed to produce ethanol from their free sugars (Ajayo et al, 2022). The tree trunks of the paper mulberry and mulberry are rich in various chemical constituents, including cellulose, hemicellulose, lignin, waxes and gums, which are widely used in the production of paper and fibre products (Jitjaicham and Kusuktham, 2016).…”
Section: Distribution and Multifunctional Utilization Of Woody Plantmentioning
confidence: 99%
“…Fruit juices were also reported as potential bio-EtOH production systems with high EtOH concentrations reported. 68,75,104 For example, paper mulberry fruit juice was studied as a bio-EtOH feedstock by Ajayo et al, where a high bio-EtOH concentration of 73.69 g L −1 , a high yield of 0.48 g g −1 to sugar and high productivity of 4.7 g L −1 h −1 were recorded. The advantage of using food crops for bio-EtOH production is their usual abundance and low-prices in certain areas.…”
Section: Ethylenementioning
confidence: 99%
“…Apart from sugarcane and corn grains, other reported crops include wheat, potato, sweet potato, cassava, bamboo shoot, sugar beet, ,, grape and cactus, for which a range of pre-treatment processes and fermentation systems were employed. Fruit juices were also reported as potential bio-EtOH production systems with high EtOH concentrations reported. ,, For example, paper mulberry fruit juice was studied as a bio-EtOH feedstock by Ajayo et al , where a high bio-EtOH concentration of 73.69 g L –1 , a high yield of 0.48 g g –1 to sugar and high productivity of 4.7 g L –1 h –1 were recorded. The advantage of using food crops for bio-EtOH production is their usual abundance and low-prices in certain areas.…”
Section: Olefin and Styrenic Monomersmentioning
confidence: 99%
“…Nowadays, the population increases and faces decreasing in traditional universal energy demand for world energy production from fossil fuels. Ajayo et al (2022) found that Ethanol from cellulosic biomass could be a promising substitute for petrol and has good octane, which leads to lessened emissions of air pollutants. Berlowska et al (2016) sugar beet pulp SBP could provide an alternative feedstock for ethanol production.…”
Section: Introductionmentioning
confidence: 99%